Tantangan dan Peluang Penyandang Disabilitas Fisik di Kota Bandung dalam Memperoleh Pekerjaan di Masa Covid-19 - Didan Akbar Zaelani; Divo Sangrila Yusuf; Ade Yunita Mafruhat; Wiedy Yang Essa (Institut Teknologi Sepuluh Nopember, 2022)
This article seeks to identify the barriers to employment, as well as the opportunities and rights fulfilment for those with physical impairments in the City of Bandung during the Covid-19 period. It's intriguing to talk about the chances and difficulties people have; they worry about obtaining work in the Covid-19 era. The descriptive qualitative approach of data analysis employed in this study refers to the events that occurred and data collection methods using interviews, observations, and documentation. By interviewing 22 people with physical disabilities in the city of Bandung. The results of the article show that labor absorption and policies to fulfil the right to work for people with physical disabilities in Bandung City have not been optimal, with six challenges faced, including limited information related to employment and training, low self-confidence, negative stigma, educational background, job opportunities and skills. On the other hand, there are four opportunities for people with physical disabilities in the city of Bandung to find work, including the government monitoring the absorption of workers with disabilities, the availability of job seekers applications, the ability to work for people with physical disabilities and the implementation of training programs.